Hydrodynamic hyperpolarization of endothelial cells. - Nakache, M (1988)
The orientation and morphology of the endothelium lining the cardiovascular system may result from hemodynamic forces acting on the endothelial cells. To investigate the flow effects at the membrane level, we have examined the variations of the fluorescence intensity of two membrane-sensitive dyes, merocyanine 540 and bis(1,3-diethylthiobarbiturate)trimethineoxonol, (i) as a function of flow shear stress and (ii) with the onset or cessation of the flow. We found a time-dependent decrease in fluorescence intensity with the onset of the flow with an exponential approach to steady state of the order of 1 min. The process is reversible; when the flow is stopped the fluorescence intensity returns to its original value. The polarization of the endothelial cell membranes or, more precisely, the amplitude of the fluorescence intensity responses is an increasing function of the shear stress (up to 120 dynes/cm2). Assuming the equilibrium potential for K+ is more hyperpolarized than the resting potential and using valinomycin, we have deduced from the sign of the ionophore effects that the flow hyperpolarizes the endothelial cell membrane.